Island Dorsalis Pedis Flap - Dr. B.K. Sharma; Dr. P.K. Verma (Indian Journal of Plastic Surgery, 1993)
The Island Dorsalis pedis Flap is used for reconstruction of defects near the lower end of tibia and area adjacent to ankle joint. The flap is dissected as an island which aid greatly in increasing its arc of rotation and in improving its manouverability. The results are satisfactory functionally with acceptable donar site morbidity.